The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.scitotenv.2021.150208
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal osmoregulatory mechanisms differ in Mediterranean and Atlantic European sea bass: A focus on hypersalinity

Abstract: European sea bass (Dicentrarchus labrax) migrate towards habitats where salinity can reach levels over 60‰, notably in Mediterranean lagoons. D. labrax are genetically subdivided in Atlantic and Mediterranean lineages and have evolved in slightly different salinities. We compared Atlantic and West-Mediterranean populations regarding their capacity to tolerate hypersalinity with a focus on the involvement of the intestine in solute-driven water reabsorption. Fish were analyzed following a two-week transfer from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…PCA results were obtained from the posterior intestine for gene expression levels of avtr and itr that showed different expression levels between conditions ( avtrv1a2 , avtrv1a1 , avtrv2b1 , itr1 ) as well as Na + /K + -ATPase (NKA) activity and expressions of genes involved in ion transport and water balance previously analyzed in the same individuals by Cao et al [ 36 ] that showed different expression patterns between conditions (aquaporins: aqp1a , aqp1b , aqp8b , aqp8ab , aqp8aa , aqp10b , Na + /K + -ATPase α1a ( nkaα1a ) and Na + /K + /2Cl − cotransporter 2 ( nkcc2 )) ( Figure 5 ). Principal component 1 (PC1) described 43.9% of the original information whereas PC2 described 17.8%, making a cumulative percentage of 61.7%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PCA results were obtained from the posterior intestine for gene expression levels of avtr and itr that showed different expression levels between conditions ( avtrv1a2 , avtrv1a1 , avtrv2b1 , itr1 ) as well as Na + /K + -ATPase (NKA) activity and expressions of genes involved in ion transport and water balance previously analyzed in the same individuals by Cao et al [ 36 ] that showed different expression patterns between conditions (aquaporins: aqp1a , aqp1b , aqp8b , aqp8ab , aqp8aa , aqp10b , Na + /K + -ATPase α1a ( nkaα1a ) and Na + /K + /2Cl − cotransporter 2 ( nkcc2 )) ( Figure 5 ). Principal component 1 (PC1) described 43.9% of the original information whereas PC2 described 17.8%, making a cumulative percentage of 61.7%.…”
Section: Resultsmentioning
confidence: 99%
“…PCA analysis showed that there was a strong correlation between avtrv1a2 and the main ion transporters (NKA activity and expression of nka α1a , nkcc2 ) involved in ion uptake in the posterior intestine. We have previously shown that the expression of nka α1a , nkcc2 and NKA activity was high in Mediterranean and Atlantic sea bass challenged to HSW [ 36 ]. The aquaporins, aqp8ab and aqp8aa , were also correlated with avtrv1a2 and main ion transporters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations